Study of competitive interactions between ectomycorrhizal and saprotrophic fungi and its effects on chestnut tree performance - Pereira, Eric (2011)
European chestnut tree (Castanea sativa Mill.), as fruit and wood producers, have a great economic importance in Trás-os-Montes region (Northeast of Portugal). In this agro-ecosystem, the Hypholoma fasciculare and the Pisolithus tinctorius are the most commonest fungi among the saprophytic and mycorrhizal trophic groups, respectively. Although, interactions between ectomycorrhizal and saprotrophic fungi have been previously observed, their effects on plant growth and health are scarcely known. Therefore, the aim of the present work was to assess the effect of the interaction between P. tinctorius and H. fasciculare on growth, nutritional status and physiology of C. sativa seedlings. In pot experiments, C. sativa seedlings were inoculated with P. tinctorius and H. fasciculare individually or in combination. Plants inoculated with P. tinctorius showed a higher growth and an increased foliar-N, -P, and photosynthetic pigment contents. These effects were suppressed when H. fasciculare was simultaneously applied with P. tinctorius. However, when plants were inoculated with P. tinctorius and after 30 days with H. fasciculare the same parameter values were very close to those from plants only inoculated with P. tinctorius. These results are most probably due to the interaction between P. tinctorius and C. sativa roots and the ability of mycorrhizae formation before H. fasciculare application. Once formed, the chestnut seedlings are able to take advantage from the mycorrhizal association. This work confirms the antagonistic interaction between ectomycorrhizal and saprotrophic fungi and demonstrates that fungal interactions affect the physiological processes of the ectomycorrhizal host.